MENUJU DISTRIBUSI RASKIN YANG ADIL (STUDI PELAKSANAAN PROGRAM RASKIN DI KABUPATEN GRESIK TAHUN 2015) - Sri Kamariah (Jurnal Public Policy, 2016)
The purpose of this study is to find out about the distribution of Raskin and fakror-Perform analysis of what factors influence the implementation Raskin and Conducting an analysis of alternative management model or pattern Raskin  orward, to ensure a fair distribution in the District Sidayu Sukorejo village,  istrict Gresik. The method is descriptive qualitative method, in which the main instrument is the researcher's own research. Source of data used is the primary data source and secondary data relating to the circumstances of the empirical implementation of policy. In this study, the authors also use survey research to obtain primary data on the distribution of Raskin. on the basis of existing data, the authors attempt to describe / illustrate a systematic, factual and accurate information on the facts, properties and relationships between phenomena. The results showed that using the frameworks of Edward III, bureaucratic structure, communication, and disposition of resources, implementation of program distribution Raskin conducted by Bulog in targeting encountered an error target (mistargeting) despite the relatively low levels, are often not appropriate because it concerned certain groups, rationing is not in accordance with the Policy Raskin Raskin is to share equally on all citizens. Recommendations include the data necessary to analyze back associated RTS-PM Raskin is not on target, RTS By rule-PM receives Raskin as much as 15 kg per month. In fact in the field, the distribution is often not appropriate number. Raskin quota should not be generalized, to be adjusted by the number of family members RTS-PMKeywords: Distribution Raskin, public policy